2013
DOI: 10.1093/llc/fqt050
|View full text |Cite
|
Sign up to set email alerts
|

Towards a digital geography of Hispanic Baroque art

Abstract: In this article we propose an approach to the study of art history based on geography of Hispanic Baroque art by digital means that showcase the multiplicity of possible places of art. Our study advances four elements of a digital geography of art (communities, semantic maps, areas, and flows)-a methodology that can be expanded in future Digital Humanities research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 5 publications
0
1
0
1
Order By: Relevance
“…Their study demonstrated how visualization facilitated the original scholarly research by employing rich data sets. Suárez et al (2013) used visualization techniques to explore another aspect of history: the authors studied art history based on the geography of Hispanic Baroque art. For example, visualizations were used to illustrate the evolution of similarity clusters in artwork throughout three different centuries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their study demonstrated how visualization facilitated the original scholarly research by employing rich data sets. Suárez et al (2013) used visualization techniques to explore another aspect of history: the authors studied art history based on the geography of Hispanic Baroque art. For example, visualizations were used to illustrate the evolution of similarity clusters in artwork throughout three different centuries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sin embargo, si no fuera posible establecer esas redes culturales, la vida humana no sería posible tal y como la conocemos. Hacerlas visibles, es decir, sacar a la supercie tanto la red subyacente (dibujarla y explicarla) como los fenómenos culturales latentes de cualquier red -por ejemplo, la red cultural y simbólica que se desarrolló y viajó con el arte barroco hispano en los siglos XVI a XVIII (Sancho-Caparrini et al, 2012;Suárez et al, 2013)-, son dos de áreas fundamentales de la incipiente disciplina de las redes culturales. Se trata no tanto de identicar objetos o individuos, sino de localizar, analizar y dibujar las relaciones entre ellos para intentar entender y explicar cómo esas relaciones han contribuido a la creación o expansión de un fenómeno cultural; a la signicación de un suceso histórico o a su desaparición en el agujero negro de la historia; a la repetición de rituales comunitarios que presentan y representan la red cultural original, a través del tiempo de la comunidad, o a la irrupción de la creatividad de un individuo en torno a un objeto o práctica cultural determinada.…”
unclassified